2019
DOI: 10.1002/chem.201901333
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Perfluorinated Phenoxyphosphorane and Conversion to Its Hexacoordinate Anions

Abstract: We report the synthesis and structuralc haracterization of an eutralP V Lewis acid, P(OC 6 F 5 ) 5 ,a nd salts containing the six-coordinate anions[ P(OC 6 F 5 ) 5 F] À and [P(OC 6 F 5 ) 6 ] À . The latter anion exhibits ar are example of F-p arene interactions in both the solid and the solution phase, which has been quantitativelys tudied by variable-temperature (VT) NMR spectroscopy.T he Lewis acid strength of P(OC 6 F 5 ) 5 has been assessed throughe xperimentalf luoridei on competi-tion experiments and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…To assess whether the significantly smaller and negatively charged fluoride ligand reveals different acidity trends compared to the neutral and larger ONMe 3 , we have calculated the FIA for the full set of Lewis acids studied here (Figure 7). Previous work has revealed some limitations of FIA values as indicators of absolute Lewis acidity when calculations have been performed in the gas phase (without a solvent model), 95 but relative Lewis acidity can be reasonably predicted through gas-phase calculations. 15,84 For consistency with the rest of the calculations in this study and other studies in this field, only the gas-phase FIA values are reported here.…”
Section: ■ Computational Methodsmentioning
confidence: 88%
“…To assess whether the significantly smaller and negatively charged fluoride ligand reveals different acidity trends compared to the neutral and larger ONMe 3 , we have calculated the FIA for the full set of Lewis acids studied here (Figure 7). Previous work has revealed some limitations of FIA values as indicators of absolute Lewis acidity when calculations have been performed in the gas phase (without a solvent model), 95 but relative Lewis acidity can be reasonably predicted through gas-phase calculations. 15,84 For consistency with the rest of the calculations in this study and other studies in this field, only the gas-phase FIA values are reported here.…”
Section: ■ Computational Methodsmentioning
confidence: 88%
“…A third flaw of the FIA transpires when it comes to the interpretation of solution‐phase experimental data. Since the fluoride ion binding reaction necessarily involves charged species, it is strongly affected by solvation energies – both for cationic and neutral Lewis acids . However, FIA have been computed commonly in vacuum only.…”
Section: Introductionmentioning
confidence: 99%
“…F : The title compound was synthesized according to an adapted procedure for LiOPh F given in the literature. [21] In this case 3.00 g p-heptafluorocresol (12.82 mmol, 1.00 equiv.) were dissolved in 50 ml hexane and 5.13 ml 2.5 m nBuLi solution in hexane (12.82 mmol, 1.00 equiv.)…”
Section: Methodsmentioning
confidence: 99%